On accuracy of simulation of gaussian stationary processes in L2([0, T]) - Turchyn, Y. (Інститут математики НАН України, 2006)
A theorem about simulation of a Gaussian stochastic process with given accuracy and reliability in L2([0, T ]) using wavelets has been proved.